Composition and diversity of weedy rice species in lowland irrigated rice field of Argao, Cebu, Philippines - EDGARDO P. LILLO; MARIA LEVY M. CHAVEZ; ARCHIEBALD B. MALAKI; STEVE MICHAEL T. ALCAZAR; RAYNILDA R. BAOY; MARVIN A. MARGATE; MICHELLE ABRIGANA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Lillo EP, Chavez MLM, Malaki AB, Alcazar SMT, Baoy RR, Margate MA, Abrigana M. 2022. Composition and diversity of weedy rice species in lowland irrigated rice field of Argao, Cebu, Philippines. Biodiversitas 23: 6275-6283. Weeds serve as a severe challenge for rice growers, causing annual crop losses worldwide. The study aims to provide baseline information on the composition and diversity of weedy rice species in lowland irrigated rice fields of Argao, Cebu, Philippines, as a basis for farmers' weed management practices. Field surveys were done using the quadrate method. A quadrate measuring 1m x 1m was randomly placed in weed-infested rice plantation areas. Weedy rice species inside the quadrate were identified. The diversity of species was computed using Shannon diversity index. A total of 53 species were recorded and classified into 21 families and 40 genera. Dominant weedy rice species during the vegetative stage was Sphenoclea zeylanica Gaertn., and Fimbristylis quinquangularis (Vahl) Kunth. for both the reproductive and harvesting stage. The site has a computed diversity value of H'=3.36 with a relative value of high species diversity, indicating less input in terms of weed management practices. The cluster analysis reveals that the lowland rice fields of Argao were covered by seven weedy rice communities. This situation could create a negative impact on rice production output. The similarity in species composition among sampling sites signifies uniformity in the application of specific weed management practices.